A praia carioca e a coluna “As garotas do Alceu”: identidades em formação (ModaPalavra e-periódico, 2010)
The column "The Girls of Alceu" circulated between 1938 to 1964 in The Cruzeiro. Weekly, the author Alceu Penna created a variety of beautiful figures, which reflected a particular lifestyle, the carioca, which spread out signs of modernity in Brazil. The intimate relationship between the "Girls" and the beaches, a traditional element of this scenario will announce an identity in formation. Being thus, this work intends to argue the relation between the Brazilian column “The Girls of Alceu” (1938-1964) and the Rio de Janeiro beaches, placing in analysis how the tanned skin starts to delineate a characteristic identity of the inhabitants of the city. The white skin of “The Girls”, but, at some moments, tanned, illustrate the lifestyle and a standard of beauty of the Rio’s women. The golden body starts also, to launch questions surrounding the identity of the Brazilian’s body.
Keywords: "The Girls of Alceu"; beaches; identity